Management of Symptomatic Uterine Arteriovenous Malformations After Gestational Trophoblastic Disease The Brazilian Experience and Possible Role for Depot Medroxyprogesterone Acetate and Tranexamic Acid Treatment - Braga, Antonio; Lima, Lana; Medeiros Parente, Raphael Camara; Celeste, Roger Keller; Rezende Filho, Jorge de; Amim Junior, Joffre; Maesta, Izildinha; Sun, Sue Yazaki; Uberti, Elza; Lin, Lawrence; Madi, Jose Mauro; Viggiano, Mauricio; et al. (Sci Printers & Publ Inc, 2018)
OBJECTIVE: To identify predictive variables of heavy vaginal bleeding from uterine arteriovenous malformation (uAVM) after gestational trophoblastic disease (GTD) and review outcomes with different treatment strategies. STUDY DESIGN: This is a retrospective study of patients with uAVM presenting with vaginal bleeding after postmolar follow-up or treatment for postmolar gestational trophoblastic neoplasia, with normal hCG levels for at least 6 or 12 months, respectively, followed at 9 Brazilian GTD reference centers, from January 2004-January 2016. Patients were treated preferentially with uterine artery embolization (UAE), but when UAE was not available, depot medroxyprogesterone acetate and tranexamic acid (DMPA + TA) was offered. RESULTS: The incidence of symptomatic uAVM after GTD was 0.6% (39/6,129). Risk factors associated with class III-IV hemorrhage included number of previous curettages (aRR 4.23, 95% CI 1.36-13.1, p=0.013), uterine artery index of resistance <= 0.32 (aRR 35.2, 95% CI 3.58-347.5, p=0.002), and uterine artery peak systolic velocity >= 78.7 cm/s (aRR 10.7, 95% CI 1.15-100.6, p=0.037). Patients with class I-II hemorrhage treated with DMPA + TA had a higher rate of uAVM resolution (N=14/16 [87.5%]) versus UAE (N=4/8 [50%], p=0.033). Patients with class III-IV hemorrhage were 87% less likely to have successful treatment with DMPA + TA compared to class I-II hemorrhage (cRR 0.13, 95% CI 0.02-0.83, p=0.013). CONCLUSION: Although UAE is preferred for cases of heavy vaginal bleeding, there may be a role for DMPA + TA in the management of less severe bleeding complications.
Keywords: Brazil; depot medroxyprogesterone acetate; gestational trophoblastic disease; tranexamic acid; uterine artery embolization; uterine arteriovenous malformation